2001
DOI: 10.1111/j.1475-2743.2001.tb00005.x
|View full text |Cite
|
Sign up to set email alerts
|

A GIS based approach to modelling the effects of land‐use change on soil erosion in New Zealand

Abstract: Abstract. The problem of soil erosion is particularly evident in New Zealand, given the combination of coarse‐textured soils, steep relief, high rainfall, and intensification of agriculture. A study was undertaken to assess the effects of land use change on soil erosion and sediment transport for the Ngongotaha catchment in New Zealand's North Island, using a GIS based decision support and modelling system. Model simulations considered the effect of increased catchment area under deer farming and forestry on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…It has the same factors as the Universal Soil Loss Equation (USLE) (Wischmeier and Smith, 1978), except that the rainfall factor is a function of mean annual rainfall only (following Mitchell and Bubenzer, 1980). The NZUSLE was calibrated using published data of surfi cial erosion rates in New Zealand (Soons and Rainer, 1968;Mosley, 1980;O'Loughlin et al, 1978O'Loughlin et al, , 1980O'Loughlin, 1984;Benny and Stephens, 1985;Lambert et al, 1985;Wilcock, 1986;Dons, 1987;Wilcock et al, 1999;Cooper et al, 1992;Fahey and Coker, 1992;Smith, 1992;Smith and Fenton, 1993;Basher et al, 1997;Fahey and Marden, 2000;Rodda et al, 2001;Quinn and Stroud, 2002). NZUSLE gives the mean annual erosion rate caused by surficial erosion processes as a product of fi ve factors Figure 4 compares NZUSLE predictions with the published measurements.…”
Section: Erosion Models and Soil Organic Carbon (Soc) Contentmentioning
confidence: 99%
“…It has the same factors as the Universal Soil Loss Equation (USLE) (Wischmeier and Smith, 1978), except that the rainfall factor is a function of mean annual rainfall only (following Mitchell and Bubenzer, 1980). The NZUSLE was calibrated using published data of surfi cial erosion rates in New Zealand (Soons and Rainer, 1968;Mosley, 1980;O'Loughlin et al, 1978O'Loughlin et al, , 1980O'Loughlin, 1984;Benny and Stephens, 1985;Lambert et al, 1985;Wilcock, 1986;Dons, 1987;Wilcock et al, 1999;Cooper et al, 1992;Fahey and Coker, 1992;Smith, 1992;Smith and Fenton, 1993;Basher et al, 1997;Fahey and Marden, 2000;Rodda et al, 2001;Quinn and Stroud, 2002). NZUSLE gives the mean annual erosion rate caused by surficial erosion processes as a product of fi ve factors Figure 4 compares NZUSLE predictions with the published measurements.…”
Section: Erosion Models and Soil Organic Carbon (Soc) Contentmentioning
confidence: 99%
“…The 5 AGNPS estimates upland erosion using the USLE and then uses sediment transport algorithms to simulate runoff, sediment and nutrient transport within watersheds (Aksoy & Kavvas, 2005). The usage of RUSLE in large models is mainly for the purpose of assisting with decision-making, such as prioritising land use objectives in the Philippines (Bantayan & Bishop, 1998), scenario analysis for water quality in catchments in New Zealand (Rodda et al, 2001), or delineating unique soil landscapes in Australia (Yang et al, 2007). This review addresses the complexity of the different factors, and things for 10 researchers to consider before applying R/USLE to their study area.…”
Section: Equation Version 2 (Rusle2) and The Modified Universal Soilmentioning
confidence: 99%
“…The investigation showed that the increase in vineyard caused the highest soil loss in Northeast Spain in the Mediterranean Basin from 1950s to 1990s (Martínez-Casasnovas and Sánchez-Bosch 2000). The deer farming was one of the main land use types and caused the most serious soil loss in the Ngongotaha catchment of New Zealand (Rodda et al 2001). Moreover, the studies also showed that sediment yield could be halved if deer farming was restricted to slopes under 20%.…”
Section: Introductionmentioning
confidence: 96%
“…Land cover changes and their spatial distribution influence the processes and magnitude of soil erosion. A great deal of studies reported the impacts of land cover on runoff and sediment (Lal 1996, Mushala 1997, Martínez-Casasnovas et al 2000, Wu et al 2001, Meng et al 2001, Rodda et al 2001, Van Rompaey et al 2001, Miller et al 2002, Jordan et al 2007. The investigation showed that the increase in vineyard caused the highest soil loss in Northeast Spain in the Mediterranean Basin from 1950s to 1990s (Martínez-Casasnovas and Sánchez-Bosch 2000).…”
Section: Introductionmentioning
confidence: 98%